2019
DOI: 10.1126/sciadv.aaw0946
|View full text |Cite
|
Sign up to set email alerts
|

p63 establishes epithelial enhancers at critical craniofacial development genes

Abstract: The transcription factor p63 is a key mediator of epidermal development. Point mutations in p63 in patients lead to developmental defects, including orofacial clefting. To date, knowledge on how pivotal the role of p63 is in human craniofacial development is limited. Using an inducible transdifferentiation model, combined with epigenomic sequencing and multicohort meta-analysis of genome-wide association studies data, we show that p63 establishes enhancers at craniofacial development genes to modulate their tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 81 publications
(161 reference statements)
4
62
1
1
Order By: Relevance
“…By using single-cell transcriptomic and epigenomic profiling techniques, Fan et al demonstrated that ΔNp63α binding generates open chromatin regions near or within the genes involved in epidermal fate specification of skin [ 65 ]. Furthermore, Lin-Shiao et al used p63 mutants, lacking DNA-binding activity, to demonstrate that ΔNp63α DNA binding is required to establish keratinocyte-specific enhancers [ 66 ]. During zebrafish embryo development, p63 binding occurs prior to chromatin opening at p63-binding sites (Table 1 ).…”
Section: Tp63 Acts As An Epidermal Pioneer Factor To Open Chromatin Rmentioning
confidence: 99%
“…By using single-cell transcriptomic and epigenomic profiling techniques, Fan et al demonstrated that ΔNp63α binding generates open chromatin regions near or within the genes involved in epidermal fate specification of skin [ 65 ]. Furthermore, Lin-Shiao et al used p63 mutants, lacking DNA-binding activity, to demonstrate that ΔNp63α DNA binding is required to establish keratinocyte-specific enhancers [ 66 ]. During zebrafish embryo development, p63 binding occurs prior to chromatin opening at p63-binding sites (Table 1 ).…”
Section: Tp63 Acts As An Epidermal Pioneer Factor To Open Chromatin Rmentioning
confidence: 99%
“…Data from numerous studies have demonstrated that p63, a homolog of p53, is vital for the normal development and homeostasis of epithelial tissues, in both humans and mice. For instance, heterozygous mutations in human p63 drives several developmental defects and disorders, especially skin abnormalities (47)(48)(49). In animal studies, p63 knockout led to severe anomalies in the development of epithelia and their derivatives, and even death at birth (25,50).…”
Section: Discussionmentioning
confidence: 99%
“…To identify genes commonly regulated by p63 across cell types and tissues, we employed a previously established meta-analysis approach, that has been helpful to infer core GRNs for human and mouse p53, the viral oncoprotein E7 and the cell cycle GRN (Fischer, 2019;Fischer et al, 2014Fischer et al, , 2016a. From 11 genome-wide studies (Abraham et al, 2018;Bao et al, 2015;Carroll et al, 2006;Gallant-Behm et al, 2012;Karsli Uzunbas et al, 2019;Lin-Shiao et al, 2019;Saladi et al, 2017;Somerville et al, 2018;Watanabe et al, 2014;Wu et al, 2012;Zarnegar et al, 2012) Table 2). The datasets have been obtained from knockdown (n=12) or overexpression experiments (n=4) of p63 in primary keratinocytes (n=3), the keratinocyte cell line HaCaT (n=2), the foreskin fibroblast cell line BJ (n=1), the breast epithelial cell line MCF10A (n=4), the squamous carcinoma cell lines H226 (n=2), KYSE70 (n=1), and FaDu (n=1), as well as the pancreatic ductal adenocarcinoma cell lines BxPC3 (n=1) and SUIT2 (n=1) ( Figure 1A and 1B).…”
Section: The P63 Gene Regulatory Networkmentioning
confidence: 99%
“…However, ΔNp63 has also been shown to harbor alternative TADs, that endow transactivation activity (Helton et al, 2006;King et al, 2003;Yang et al, 2006). Notably, the many ΔNp63 binding sites are associated with enhancer regions, where ΔNp63 has been proposed to "bookmark" genes that are expressed in stratifying epithelia (Karsli Uzunbas et al, 2019;Kouwenhoven et al, 2015a;Lin-Shiao et al, 2019;Qu et al, 2018;Somerville et al, 2018). Here, we focus on the most widely expressed isoforms p53α (hereafter p53) and ΔNp63 (hereafter p63).…”
Section: Introductionmentioning
confidence: 99%